An Electronic Healthcare Record Server Implemented in PostgreSQL. Issue 3 (9th September 2015) - Austin, Tony; Sun, Shanghua; Lim, Yin Su; Nguyen, David; Lea, Nathan; Tapuria, Archana; Kalra, Dipak
Abstract : This paper describes the implementation of an Electronic Healthcare Record server inside a PostgreSQL relational database without dependency on any further middleware infrastructure. The five-part international standard for communicating healthcare records (ISO EN 13606) is used as the information basis for the design of the server. We describe some of the features that this standard demands that are provided by the server, and other areas where assumptions about the durability of communications or the presence of middleware lead to a poor fit. Finally, we discuss the use of the server in two real-world scenarios including a commercial application.